2010
DOI: 10.1177/0886109910384069
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of the Waves: Wipeout or Still Riding High?

Abstract: This paper argues for feminism's enduring importance in light of social workers' daily experience of women's abuse and oppression. While cognisant of the many ways feminist theories can be understood, we examine the successive waves of feminism and apply Fraser's (1995, 2000) theory of recognition and redistribution to examine contemporary feminist movements and point to future directions for feminist social work. We argue that postcolonial feminism, with its awareness of culture and context, has most usefulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…Although some authors have suggested that feminisms' influence on social work practice, teaching, and research has been "almost breathtaking" (Shaw, 1999, p. 114), others have commented that social work lacks an appreciation for the complexities of feminisms and have called for a deeper engagement with feminist theories (Orme, 2003;Sands & Nuccio, 1992). Despite having related with all three feminist waves to different degrees (Gray & Boddy, 2010), some suggest that liberal, radical, and postmodern feminisms (Freeman, 1990;Kemp & Brandwein, 2010;Nes & Iadicola, 1989) characterizing feminism's second wave have had a greater influence on social work theory and discourse than has third-wave feminist discourses of cultural studies, postfeminism, and postcolonial feminist theory (see Baines, 1997;Barnoff & Moffatt, 2007;Orme, 2003;Sands & Nuccio, 1992).…”
Section: Theory In Feminist Social Work Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…Although some authors have suggested that feminisms' influence on social work practice, teaching, and research has been "almost breathtaking" (Shaw, 1999, p. 114), others have commented that social work lacks an appreciation for the complexities of feminisms and have called for a deeper engagement with feminist theories (Orme, 2003;Sands & Nuccio, 1992). Despite having related with all three feminist waves to different degrees (Gray & Boddy, 2010), some suggest that liberal, radical, and postmodern feminisms (Freeman, 1990;Kemp & Brandwein, 2010;Nes & Iadicola, 1989) characterizing feminism's second wave have had a greater influence on social work theory and discourse than has third-wave feminist discourses of cultural studies, postfeminism, and postcolonial feminist theory (see Baines, 1997;Barnoff & Moffatt, 2007;Orme, 2003;Sands & Nuccio, 1992).…”
Section: Theory In Feminist Social Work Researchmentioning
confidence: 97%
“…Researchers who have recently explored in a broad manner the relationship between theory and feminist practice/research (Gray & Boddy, 2010;Gringeri, Wahab, & Anderson-Nathe, 2010;Kemp & Brandwein, 2010;Orme, 2003) agree that some of the current theoretical (and practical) tensions among feminisms revolve around essentializing claims about oppression within critical theories and postmodern and poststructuralist rejection of grand narratives and theories, as well as binaries.…”
Section: Theory In Feminist Social Work Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Participants then read true information about gender-based dif- N = 137), the effect of self-respect on normative collective action is not significant (β = .17, p = .053; r bivariat = .16, p = .054; see Appendix S2 ), suggesting that the psychological processes underlying collective action towards gender equality might indeed be different for hetero-and homosexual women. One difference might lie in differing priorities on redistribution versus social recognition (e.g., Gray & Boddy, 2010), which could be explored in future research that should also try to use larger subsamples of homosexual participants in order to test for statistical moderation.…”
Section: Inequality Scenariomentioning
confidence: 99%
“…Feminist theory, the strengths perspective, ecosystems theory, and social groupwork theory informed the study. Feminism's critical perspective highlighted the way in which women's experiences were shaped by structural, historical, and contextual conditions in their lives (Gray & Boddy, 2010). The researcher recognised that structural barriers would affect the women in the study -who were all from low socioeconomic backgrounds -by impeding personal development and social progression.…”
Section: Theoretical Frameworkmentioning
confidence: 99%